A feasibility study on The Student Lounge a study place and food establishment in Katipunan Avenue, Quezon City - Cabardo, Phillip Rey A.; Caranguian, Honey Lynne M.; Manso, Ana Christabel J.; Maximo, Edward Vincent G. (Quezon City College of Engineering, University of the Philippines Diliman, 2009)
This paper is a feasibility study on The.Student.Lounge or simply TSL. This is a Katipunan-based, 24-hour open, food establishment with the environment of a student's study place and provided with the services of a computer shop. It provides a place for students to study, have group meetings, make projects and is a place to eat and stay for 24 hours. It has the following Mission and Vision statements. Mission: To provide a study sanctuary for the customers by providing them with consistent excellent service and not just presenting them with quality food but a great staying experience as well. Vision: To be the study area of choice, outside school and home, in Katipunan Avenue especially for university students, by providing them with excellent food service and an ideal place for them to study and complete their academic requirements. This paper consists of five feasibility studies namely: Market Study, Technical Study, Organizational and Management Study, Financial Study and Social Profitability Study. In the market study, it was determined whether the business idea has a market to be targeted. Along with the study is the creation of the marketing strategies. It was determined that the target market of The.Student.Lounge are the college students who prefer studying at fast food establishments. Preferably, they are students from UP Diliman, Ateneo de Manila University and Miriam College, the closest schools to the establishment. Non-students who bring and use their laptops at similar establishments are also included in the market. Specifically, 30.05% of the current market is targeted. This comprises the percentage of customers who study at coffee shops and fast food areas, and the percentage of the customers who are willing to try The.Student.Lounge. These are based on the survey results given out to the customers. From the technical study, it was decided that the business will be established at Katipunan Avenue, beside the stores of Red Ribbon and Kenny Roger's Roasters. It is in front of Ateneo de Manila University and near an overpass to the said school. The.Student.Lounge has a maximum capacity of 111 seats. The expected utilization of food-buying customers over the total number of customers is 50%. Different scenarios are expected for the number of customers that will be coming to TSL. Given these scenarios, the capacity of the establishment can still accommodate the maximum number of expected customers to come, because the expected number of people was not too low nor does it go over 111 people. Costing was done on the products to be offered by TSL. After including the markup percentage and Value Added Tax, the food was priced at an average of Php80 per meal, which is within the range of the amount that the surveyed students are willing to spend. One of the reasons why a company is successful is that they have an appropriate organizational and management structure. The organizational and management structure of TSL was determined and the form of the organization would be a general partnership where the managers are the owners, and that there will be a single assigned general manager. At least 18 people will be needed for the manpower of The.Student.Lounge, and can reach up to 25 people for predicted high-demand periods. A financial study is conducted for the generation of statement of accounts. These accounts will be the basis for the determination of the profitability of the business. Also, it was proven that all the needed supplies and equipments for the operation of TSL are accessible and can be invested on to bring profit to the owners of the business. Estimated investment requirement is at Php1 ,800,000, payback period at 19 months and from the positive value of the computed Net Present Value, it was proved that the investment is worth it. Lastly, from the social profitability study, the advantages and disadvantages that TSL will be contributing to the market, the community, and the country was thoroughly analyzed. Establishment of The.Student.Lounge would not only give convenience to its customers but would add to the entrepreneurial activities in the city and is expected to contribute a total of Php 917,586.56 in taxes to the governments for the next five years. It will also be providing jobs for at least 18 people, and contribute to the sales of its suppliers daily. With the satisfying results of each of the five studies, The.Student.Lounge has proved to be a marketable, technically-feasible, manageable, financially-feasible and socially-profitable business idea.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Cybercafes -- Philippines -- Quezon City; Feasibility studies